Improve basic physics learning using the Jupyter Notebook App - Panjaitan, Melda; Hutagalung, Siti Nurhabibah (Institute of Computer Science (IOCS), 2025)
Basic Physics learning often faces challenges in improving students' conceptual understanding and analytical skills. The Jupyter Notebook application, which offers a Python-based interactive environment, is an innovative alternative to solve this problem. This study aims to evaluate the effectiveness of the use of Jupyter Notebook in learning Basic Physics in first-year students in college. The research method used is quasi-experimental with a mixed-method approach. The results of the study show that the application of Jupyter Notebook improves students' conceptual understanding, problem-solving skills, and learning motivation.